Brothers in arms: The value of coalitions in sanctions regimes - Sonali Chowdhry; Julian Hinz; Katrin Kamin; Joschka Wanner (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper examines the impact of coalitions on the economic costs of the 2012 Iran and 2014 Russia sanctions. By estimating and simulating a quantitative general equilibrium trade model under different coalition set-ups, we (i) dissect welfare losses for sanction-senders and target; (ii) compare prospective coalition partners and; (iii) provide bounds for the sanctions potential - the maximum welfare change attainable - when sanctions are scaled vertically, i.e. across sectors up to an embargo, or horizontally, i.e. across countries up to a global regime. To gauge the significance of simulation outcomes, we implement a Bayesian bootstrap procedure that generates confidence bands. We find that the implemented measures against Iran and Russia inflicted considerable economic harm, yielding 32-37% of the vertical sanctions potential. Our key finding is that coalitions lower the average welfare loss incurred from sanctions relative to unilateral implementation. They also increase the welfare loss imposed on Iran and Russia. Adding China to the coalition further amplifies the welfare loss by 79% for Iran and 22% for Russia. Finally, we quantify transfers that would equalize losses across coalition members. These hypothetical transfers can be seen as a sanctions-equivalent of NATO spending goals and provide a measure of the relative burden borne by coalition countries.
Keywords: F13; F14; F17; F51; 330; Sanctions; Embargoes; Alliances; Sectoral linkages